2017
DOI: 10.3141/2631-06
|View full text |Cite
|
Sign up to set email alerts
|

Use of Digital Image Correlation for the Evaluation of Flexural Fatigue Behavior of Asphalt Beams with Geosynthetic Interlayers

Abstract: In this study, the flexural fatigue performance of two-layer asphalt beams with and without geosynthetic interlayers was evaluated with a digital image correlation (DIC) technique. A field scenario was simulated by considering an old, destressed pavement as the bottom layer with a compacted bituminous mix as an overlay. An appropriate tack coat and geosynthetic interlayer were at the interface. The digital images were recorded at a specific interval of load cycles during a repeated load four-point bending test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Zofka et al (8) reported that four times more energy was needed for crack propagation to break through the geosynthetic interface and the remaining portion of the HMA beam. Similar findings were found in later studies (1,9).…”
supporting
confidence: 92%
See 2 more Smart Citations
“…Zofka et al (8) reported that four times more energy was needed for crack propagation to break through the geosynthetic interface and the remaining portion of the HMA beam. Similar findings were found in later studies (1,9).…”
supporting
confidence: 92%
“…DIC is a technique for measuring deformation, displacement, and strain from a captured image set. Two-dimensional DIC analysis has proven successful for analyzing crack propagation in asphalt mixtures with geosynthetic interlayers (1). The basic function of the DIC software is to track a random pattern of particles within a determined subset size throughout the full sequence of testing images.…”
Section: Dicmentioning
confidence: 99%
See 1 more Smart Citation
“…Its ability to estimate strains with reasonable accuracy has been well documented with experimental validation using strains measured by devices such as strain gauges (Gothekar, ; Rutkiewicz & Jakobczak, ; Sadek et al, ). In particular, DIC proved to be efficient in detecting microcracks in geomaterials (Kumar & Saride, ; Sause, ). Particularly, it was shown that for in‐plane and small‐strain measurements (such as in this study), DIC is very accurate (Acciaioli et al, ; Hoult et al, ).…”
Section: Experimental Methodologymentioning
confidence: 99%
“…Although the use of geosynthetics for reinforcement of asphalt pavement has been verified by most researchers in various aspects [ 21 , 22 , 23 ], the evaluation of the reinforced effect varies with the research content. For example, the improvement of crack resistance of geosynthetics is often ignored when analyzing its inhibition of reflection crack, and its effect on rutting resistance is also ignored when analyzing its anti-crack performance [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%